A Deficit in Movement-Derived Sentences in German-Speaking Hearing-Impaired Children - Ruigendijk, Esther; Friedmann, Naama (Frontiers in Psychology, 2017)
Children with hearing impairment (HI) show disorders in morphology and syntax. The question is whether and how these disorders are connected to problems in the auditory domain. The aim of this paper is to examine whether moderate to severe hearing loss at a young age affects the ability of German-speaking orally trained children to understand and produce sentences. We focused on sentence structures that are derived by syntactic movement, which have been identified as a sensitive marker for syntactic impairment in other languages and in other populations with syntactic impairment. Therefore, our study tested the repetition and/or comprehension of subject and object relatives, subject and object Wh-questions, passive sentences, and topicalized sentences, as well as sentences with verb movement to second sentential position. We tested 19 HI children aged 9;5-13;6 and compared their performance with hearing children using sentence-picture matching and sentence repetition tasks. For the comprehension tasks, we included HI children who passed an auditory discrimination task; for the sentence repetition tasks, we selected children who passed a screening task of simple sentence repetition without lip-reading; this made sure that they could perceive the words in the tests, so that we could test their grammatical abilities. The results clearly showed that most HI children had considerable difficulties in the comprehension and repetition of sentences with syntactic movement: they had significant difficulties understanding object relatives, Wh-questions, and topicalized sentences, and in the repetition of object who and which questions and subject relatives, as well as in sentences with verb movement to second sentential position. Repetition of passives was only problematic for some children. Object relatives were still difficult at this age for both HI and hearing children. An additional important outcome of the study is that not all sentence structures are impaired—passive structures did not pose a problem for the HI children in comprehension, and caused fewer problems in repetition than other structures.